Dynamic Changes in Quantitative Features of Human Gastric Lesions - Ventzeslav Enchev; Jean Paul Rigaut (Analytical Cellular Pathology)
Quantitative DNA, morphometric cellular and nuclear variables were evaluated in surgical biopsies from patients with various gastric lesions: chronic gastritis, chronic ulcers, adenomatous polyps (gastric adenomas), primary carcinomas and their corresponding lymph‐node metastases. Paraffin‐embedded tissue sections were studied by static cytophotometry (plug method), karyometry (measurements with a graduated eyepiece micrometer of the major and minor axes of the elliptic nuclear profiles, and calculation of profile areas), and measurements of cellular profiles (largest and smallest caliper diameters). Tissue lymphocytes from the same slide were used as diploid controls for the DNA evaluations.